Legal Protection for Witnesses in The Criminal Act of Theft Based on The Criminal Code (KUHP) - Tarigan, Hendra Julianto Marselinus; Aspan, Henry; Zarzani, Riza (JURNAL HUKUM SEHASEN, 2026)
The crime of theft as regulated in Chapter XXII, Article 362 of the Criminal Code is theft in its basic form. The elements are, namely the "objective" element, there is an act of taking, the object taken is something, the item is wholly or partially owned by another person. The crime of theft with violence is regulated in Article 365 of the Criminal Code, and also includes all the elements outlined in Article 363 paragraph 1 of the Criminal Code. This prolonged tendency has ultimately become a taboo in society. The victim is considered the party that receives help, with the assumption of punishing the perpetrator of the crime alone; unless the victim is also a witness, to help in providing evidence in the crime, the rest returns to the goal and view of punishing the perpetrator alone. In Indonesia itself, there are regulations regarding the protection of victims and witnesses, such as in Law Number 13 of 2006 concerning the Protection of Witnesses and Victims. With these regulations, witnesses and victims should receive proper guarantees and not need to feel threatened or harmed. Because victims are the ones who suffer, they should receive assistance or facilitation in reporting or filing complaints with the authorities. Therefore, this research was conducted using normative legal research (normative legal research method). The normative legal research method is a legal literature study conducted by examining literature or secondary data. This research was conducted to obtain materials in the form of theories, concepts, legal principles, and related legal regulations. The data obtained in this study will be analyzed qualitatively in accordance with the specific nature of the research, to examine the relationship between theory and practice in witness protection in theft crimes. Qualitative data analysis. Legal protection for witnesses and witnesses in theft crimes involves guaranteeing a sense of security from potential threats arising from the presence of a suspect or his accomplice. Legal protection for victims of theft crimes, although it has been implemented well, it would be better if there were efforts made by law enforcement officers in overcoming or suppressing the occurrence of violent theft crimes by conducting education on the dangers of theft crimes, patrolling, and also forming community groups that are responsive to a crime. By paying attention to law enforcement officers in making policies towards victims and witnesses, they pay more attention to the aspect of interest in this case, victims and witnesses as people who suffer physically and mentally really need all efforts or policies that support the achievement of justice that should be obtained by the victims.